GLOBAL GEOGRAPHY OF INFECTIVE ENDOCARDITIS PATHOGENS: ETIOLOGY AND RESISTANCE IN THE 21ST CENTURY - Trnkić Andrejević, Saška; Ristić, Tatjana; Čučulanović, Dejan; Ćirić Zdravković, Snežana; Nastasijević Borovac, Desa (HEALTH CARE, 2026)
Introduction/Aim: The etiology of infective endocarditis is diverse and complex. It varies significantly depending on geographical region, socioeconomic conditions, healthcare availability, and the prevalence of predisposing factors. The aim of this paper is to analyze the global geographical distribution of infective endocarditis pathogens in the 21st century, focusing on regional differences in etiology, diagnostics, therapy, and antimicrobial resistance.Methods: A secondary data analysis was conducted. Descriptive statistics were used to quantify pathogen frequency, the prevalence of resistant strains, and regional etiological differences.Results: In developed regions (North America and Western Europe), Staphylococcus aureus predominates, often associated with healthcare settings (30–35%) and high rates of MRSA resistance (up to 28%). Conversely, in developing countries, streptococci remain more prevalent, alongside the persistence of rheumatic heart disease. The availability of transesophageal echocardiography (TEE) and surgical treatment is significantly higher in developed countries, which directly contributes to a lower mortality rate (14–15%) compared to resource-limited regions (22%).Conclusion: Infective endocarditis has evolved into a disease associated with modern medicine and aging populations in developed countries, while in the rest of the world, it remains strongly associated with low socioeconomic conditions. High mortality and increasing resistance necessitate the global standardization of diagnostics and locally adapted therapeutic strategies.
Keywords: infective endocarditis, causative agents, global distribution, echocardiography